Multimodal imaging for clinical target volume definition in prone whole-breast irradiation: a single institution experience. (2nd February 2018) - Huscher, Alessandra; Santus, Dina; Soregaroli, Alberto; Mutti, Stefano; Levrini, Gabriele; Donadoni, Laura; Cascioli, Paolo; Guerini, Francesca; Prochilo, Tiziana; Aroldi, Francesca; Zaniboni, Alberto; Bignardi, Mario
Aim: The aim was identification of reference structures for breast clinical target volume (CTV) in prone position, throughout image fusion process.Materials & methods: We analyzed breast glandular tissue distribution in 20 diagnostic MRIs, referring to structures reported in ESTRO guidelines for supine irradiation. The volume containing breast glandular tissue in all cases was defined as MRI prone CTV (MRIpCTV). Then in ten subsequent patients planned for prone irradiation, MRI and computed tomography (CT) simulation was acquired. MRIpCTV was defined followed by our findings and transferred to CT for definitive delineation.Results: MRIpCTV was defined by the caudal edge of clavicular head, 3 mm above inframammary fold, by the medial thoracic artery, by a plane passing through the lateral surface of pectoralis muscles, by the anterior surface of pectoralis muscles and 3 mm from the skin. Deformed CTV was consistent with anatomy on CT; the limits chosen for MRIpCTV fit adequately also for CT.Conclusion: Prone irradiation is an alternative set up for selected cases, so the sample is very small. However, our suggestions could be of aid in defining prone CTV. The good consistency between MRI and CT seems to confirm that MRI may be unnecessary in routine practice.